2007
DOI: 10.1007/s11270-007-9460-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ozone Concentration in a Valley of the Alps Mountains Based on Bel-W3 Tobacco Leaf Injury

Abstract: The level and distribution of tropospheric ozone in remote and wildness areas of the Maurienne valley, a main axis in European transport, were determined during summertime 2004 and 2005. A comprehensive distribution of biological and chemical sensors based on the commonly used ozone sensitive Bel-W3 tobacco and the passive sampling system, was set up. A significant positive correlation was observed between the two methods and the continuous ozone monitors set in three instrumental co-locations. Moreover, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…Considering the protection of forest trees, the critical levels are set at an AOT40 value of 10,000 ppb h over 6 months (i.e., a weekly bulk average of 417 ppb h (Nali et al 2007) or 834 ppb h for 2 weeks). During our study, the average 14-day AOT40 value was significantly higher, reaching at least 900 ppb h. This ozone evolution seems to be similar to those observed in several regions in other Mediterranean countries (Lorenzini 1994;Lorenzini et al 1995;Saitanis 2003;Nali et al 2007;Laffray et al 2007). The trend in AOT40 (Fig.…”
Section: Aot40 At the Monitoring Stations During Exposure Periodsupporting
confidence: 89%
See 1 more Smart Citation
“…Considering the protection of forest trees, the critical levels are set at an AOT40 value of 10,000 ppb h over 6 months (i.e., a weekly bulk average of 417 ppb h (Nali et al 2007) or 834 ppb h for 2 weeks). During our study, the average 14-day AOT40 value was significantly higher, reaching at least 900 ppb h. This ozone evolution seems to be similar to those observed in several regions in other Mediterranean countries (Lorenzini 1994;Lorenzini et al 1995;Saitanis 2003;Nali et al 2007;Laffray et al 2007). The trend in AOT40 (Fig.…”
Section: Aot40 At the Monitoring Stations During Exposure Periodsupporting
confidence: 89%
“…The threshold ozone levels, beyond which necrosis appears, is very low i.e., 40 ppb for plant exposed for a period of 8 h (Larsen and Heck 1976). Since the beginning of the 1960s, this Bel-W3 variety has often been used as an indicator of the presence of ozone, especially in the United States (Craker et al 1974;Walter and Barlow 1974), The Netherlands (Posthumus 1976), the United Kingdom (Ashmore et al 1978(Ashmore et al , 1980, Israel (Goren and Donagi 1979), France (Bonte 1985;Van Haluwyn and Garrec 1995;Garrec and Livertoux 1997;Vergé 2000;Laffray et al 2007), Italy (Nali et al 2006, 2007), and Brazil (Sant'Anna et al 2008. However, the sensitive tobacco indicator system has never been used in ozone biomonitoring programs in North African countries because of the relatively little knowledge about plant response to air pollutants in harsh climatic and physiologic factors susceptible to alter the type and the severity of foliar symptoms (Madkour and Laurence 2002).…”
mentioning
confidence: 99%
“…This specific nature of foliar injury formation had been used worldwide for the monitoring of O 3 with different plants. Tobacco cv Bel W3, clover, and brown knapweed have established themselves as reliable and sensitive bioindicator of O 3 (Nali et al 2006(Nali et al , 2007Laffray et al 2007). Laffray et al (2007) showed that foliar injury developed in Tobacco cv Bel W3 against O 3 could be as reliable as O 3 analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…In different programs in Europe and America, injury symptoms of native plants were largely used to evaluate the relationship between O 3 exposure and effect (Manning 1997;Klumpp et al 2002;Nali et al 2007;Laffray et al 2007). Though the problem in tropical countries as India was more like other developing countries, still not much attempt of biomonitoring with plants against O 3 was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation